The Role of Public Administration in the Generation of Democratic Quality - Villoria, Manuel (Revista del CLAD Reforma y Democracia, 2016)
The combined challenges of growing inequality, crisis of the political parties system and globalization are generating problems of legitimacy for our democracies. The answer cannot be less democracy but better democracy. What could be the role of Public Administration (PA) in improving the quality of our democracies? This is the question we are trying to answer in this article. To do that, we have to begin defining and operationalizing the concept of democratic quality. Here too, it will be necessary to justify the legitimacy of PA to pursue the constitutional and legal values defined for it. Finally, once defined the values that PA must pursue and implement in a democracy (fairness, transparency, accountability, effectiveness, participation and equity), we will proceed to specify the instruments to work with. We will conclude linking such tools and values with the key variables of democratic quality, verifying their coherence and compatibility.